Adult-Onset Still's Disease (AOSD): A Case Report - Muhammad Reagan; Radiyati Umi Partan (Indonesian Rheumatology Association, 2022)
Background: Adult-Onset Still's Disease (AOSD) is a rare multisystemic autoinflammatory disorder with an unknown etiology, and the diagnosis is difficult due to various differential diagnoses. AOSD diagnosis is getting better because medical developments and therapeutic strategies from various studies have benefited from advances in understanding autoinflammatory and autoimmune diseases. Case presentation. A woman patient has a complaint of periodic high fever with joint pain for more than 1 month and reddish spots on the skin, fatigue, and menstrual disorders. Patients had been treated several times and performed a blood transfusion, but complaints still occur frequently. The patient is diagnosed with Adult-Onset Still’s Disease with secondary amenorrhoea. Conclusion: This case is rarely found, so it requires quite difficult therapy and diagnostics. Therefore, this case was presented as a case report in order to get better therapy.